Spirit Lake - Kantor, MacKinlay 1904-1977 (World Publ. Co., 1961)
A novel of Iowa in the 1850's, culminating in the Spirit Lake Massacre of '57--as seen both from the viewpoint of the Dakota Nation and that of the white pioneers.
Keywords: Spirit Lake (Iowa) -- Massacre, 1857 -- Fiction